Nexus Between Financial Development and Renewable Energy Usage in Bangladesh - Tanchangya, Tipon; Ridwan, Mohammad; Raihan, Asif; Khayruzzaman; Rahman, Md. Shoaibur; Rahman, Junaid; Foisal, Md. Zia Uddin; Mohajan, Babla; Paul, Arindrajit; Rafi, Azizul Hakim; Islam, Samanta (Journal of Environmental and Energy Economics, 2023)
Utilizing renewable energy is a method to reduce climate change and address the energy sector crisis in Bangladesh. Nonetheless, the progress of the renewable energy sector depends on monetary expansion, the accessibility of financial assets, and energy costs. This study examined the short- and long-term effects of financial development on green energy usage, accounting for energy pricing and GDP expansion. In accordance with the paper's objective, the Autoregressive Distributed Lag (ARDL) approach was utilized, employing data from 1990 to 2021. The results demonstrated that financial development promotes clean power utilization in Bangladesh, but energy expenses and economic growth exert a detrimental impact. This study significantly contributes to renewable energy literature and facilitates policymakers in exploring alternate energy supplies to meet the country’s increasing electricity demands.